HUBUNGAN GAYA KEPEMIMPINAN DEMOKRATIS DAN MOTIVASI KERJA DENGAN KINERJA GURU DI YAYASAN PANGUDI LUHUR CABANG SURAKARTA - Mugiyanto Albertus, Sutarno & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT The research population is taken from 110 teachers of Pangudi Luhur Institution, which are Pangudi Luhur 1, 2, 3 elementery schools, Pangudi Luhur â€œ Bintang Lautâ€ Junior High School, and Pangudi Luhur â€œSanto Yosefâ€ Senior High School. The samples are 50 teachers, which is taken through proportional cluster random sampling. The samples are 50 teachers, which is taken through proportional cluster random sampling. The writer uses the validity and reliability questionnaire test in collecting data. The data processing uses product moment correlation and double correlation which is processed by SPSS 12,00 program. The analytical results show that: (1) The r test to X1 shows that the average of r is 0,431 with r table 0,297, (2) The test result of r average to X2 shows that 0,471 with r table 0,297, therefore there is a positive and significant partially relation between the X1 and X2 variable. (3) The result of F average is 7, 455 since the signification less then 5 percent therefore there is a positive and significant relation between X1 and X2 variable with Y.(4) The result of the r test for the coefficient correlation X1 and Y is 0,431.The t test for the coefficient correlation X2 and Y is 0,471 therefore there is a closer relationship between the working motivation and the teachers performance. Keywords: democratic leadership style, working motivation, teachers performance.